Low-temperature low-dielectric-loss microwave dielectric ceramic CoTeMoO6 and preparation method thereof
By using low-temperature sintering technology in the preparation of microwave dielectric ceramic CoTeMoO6, the problems of large energy consumption and poor performance caused by high sintering temperature in traditional methods are solved, low dielectric loss and efficient preparation are achieved, and the microwave dielectric of the material is improved performance.
Patent Information
- Application Number
- CN202411525845.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The high sintering temperature in traditional microwave dielectric ceramic materials preparation methods leads to large energy consumption and material performance. Low-temperature sintering technology needs to be explored to reduce energy consumption and optimize material performance.
A low-temperature and low-dielectric loss microwave dielectric ceramic CoTeMoO6 is used to prepare a low-temperature and low-dielectric loss microwave dielectric ceramic CoTeMoO6. By mixing cobalt monoxide, tellurium and molybdenum powders at 1:1:1, ball milling and drying, and after pre-sintering, PVA adhesive is added. Pressed molding and sintered under ultra-low temperature conditions to achieve optimization of dielectric performance.
The low-dielectric loss microwave dielectric ceramic CoTeMoO6 was successfully prepared under ultra-low temperature sintering conditions of 500-620°C, which significantly reduced energy consumption, shortened the preparation cycle, improved production efficiency, and improved the microwave dielectric performance of the material.
Smart Images

Figure CN119263827A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of microwave dielectric ceramic materials, in particular to a low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6 and a preparation method thereof. Background Art
[0002] ULTCC technology (Ultra Low Temperature Co-fired Ceramics) is a new type of multilayer ceramic technology. With its unique advantages of ultra-low temperature sintering, this technology not only significantly reduces energy consumption and production costs, but also greatly broadens the integration possibilities of conductor materials and semiconductor components. The wide application of ULTCC technology, from sophisticated wireless communication equipment to complex automotive electronic systems to the demanding aerospace field, has demonstrated its unparalleled performance advantages. In the field of communications, ULTCC components have become key components for improving communication efficiency and quality with their high-frequency characteristics and low-loss performance. They are widely used in core components such as filters and antennas, providing strong support for high-speed data transmission and long-distance communication. In the field of automotive electronics, ULTCC technology provides a reliable solution for the manufacture of automotive electronic components with its excellent high temperature resistance, vibration resistance and corrosion resistance. In the field of aerospace, ULTCC technology has become one of the key technologies in the manufacture of aerospace electronic equipment with its outstanding performance and wide range of applications. With its unique advantages and broad application prospects, ULTCC technology is gradually becoming an important force in promoting the development of the electronic component manufacturing industry. With the continuous advancement of technology and the continuous expansion of the market, ULTCC technology will surely usher in a broader development space and a more brilliant future.
[0003] In the current field of microwave dielectric ceramic material preparation, although many advances have been made, traditional methods generally face the challenge of high sintering temperatures. High-temperature sintering not only consumes a lot of energy, but may also affect the microstructure and final performance of the material. Therefore, exploring low-temperature sintering technology to reduce energy consumption and optimize material performance has become a research hotspot in this field. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6 and a preparation method thereof.
[0005] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0006] One of the purposes of the present invention is to provide a method for preparing low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6, comprising the following steps:
[0007] S1, taking cobalt monoxide powder, tellurium dioxide powder and molybdenum trioxide powder in a molar ratio of 1:1:1, and mixing them uniformly to obtain a mixed powder A;
[0008] S2, adding the mixed powder A into deionized water, and performing the first ball milling to obtain a mixed slurry A;
[0009] S3, drying the mixed slurry A, and passing it through a 40-80 mesh sieve after drying to obtain granular powder of a suitable size, thereby obtaining a mixed powder B;
[0010] S4, heating the mixed powder B to 400°C and pre-sintering for 5.5-6 hours to obtain mixed powder C;
[0011] S5, adding the mixed powder C into deionized water, and performing a second ball milling to obtain a mixed slurry B, drying the mixed slurry B, and passing it through a 40-80 mesh sieve after drying to remove large particles of impurities, thereby obtaining a mixed powder D;
[0012] S6, adding 8 wt % of PVA adhesive to the mixed powder D, grinding thoroughly until uniformly mixed, and passing through an 80-110 mesh sieve to obtain a mixed powder E; pressing the mixed powder E into a shape;
[0013] S7. After the formed block is allowed to stand at room temperature for 8-10 hours, it is placed in a sintering furnace, heated to 480°C, and maintained for 6 hours to volatilize the PVA adhesive; then, the temperature is continued to be raised to 500-620°C and sintered for 2-4 hours, and the furnace is cooled to room temperature to obtain a low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6.
[0014] Furthermore, the particle sizes of the cobalt monoxide powder, tellurium dioxide powder and molybdenum trioxide powder are all 350-400 meshes, and the purity of the cobalt monoxide powder, tellurium dioxide powder and molybdenum trioxide powder are all 99.0%-99.95%.
[0015] Furthermore, during the first and second ball milling, an appropriate amount of deionized water is added to the ball mill to fully wet the powder, and the powder is allowed to stand for 15-18 hours to promote water penetration between particles; after the gas in the tank is removed, the ball mill is started for 20-24 hours of continuous ball milling to obtain a fine and uniform slurry.
[0016] Preferably, the mixed slurry A and the mixed slurry B are both dried at 80-95°C.
[0017] Preferably, in step S4, heating is performed to 400° C. at a heating rate of 5° C. / min.
[0018] Preferably, in step S6, the material is pressed into a cylindrical block at a pressure of 2 bar.
[0019] Preferably, in step S7, the sintering temperature is 560-600°C.
[0020] The second object of the present invention is to provide a low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6 prepared by the above method.
[0021] Compared with the prior art, the present invention synthesizes ultra-low loss CoTeMoO6 ceramics under ultra-low temperature sintering (only 500-620°C) conditions on the basis of the traditional solid phase method, which not only greatly reduces energy consumption, but also significantly shortens the overall cycle from material preparation to finished product; the adoption of this low temperature sintering technology makes the entire production process more efficient and faster, and the production cycle is short, which improves production efficiency and reduces production costs; the CoTeMoO6 ceramics prepared by the present invention have good microwave dielectric properties: the dielectric constant ε r =11.36-13.88, quality factor and frequency product Q×f=6849-44110GHz, temperature coefficient τ f =-90.8-72.4ppm / ℃, these characteristics make it possible to be used in microwave devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the X-ray diffraction (XRD) pattern analysis of CoTeMoO6 ceramic material at different sintering temperatures in the range of 500℃ to 620℃.
[0023] Figure 2 SEM microstructure images of CoTeMoO6 ceramics sintered at 500-620℃ and Gaussian fitting curve of its grain size distribution.
[0024] Figure 3 It characterizes the change trend of density and relative density of CoTeMoO6 ceramic material in the sintering temperature range of 500℃ to 620℃. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.
[0026] The test methods in the following examples are conventional methods unless otherwise specified. Unless otherwise specified, the reagents and materials used can be obtained through commercial channels.
[0027] Example 1
[0028] 1. Raw material selection and mixing
[0029] Raw material selection: Select CoO powder (purity of 99.95%), TeO2 powder (purity of 99.9%) and MoO3 powder (purity of 99.9%) in the particle size range of 350-400 mesh.
[0030] Proportioning and mixing: Weigh CoO powder, tellurium TeO2 powder and molybdenum MoO3 powder in a molar ratio of 1:1:1, mix them evenly, and transfer them to a ball mill for later use.
[0031] 2. Wet grinding and pre-sintering
[0032] Preparation for wet grinding: Add appropriate amount of deionized water to the ball mill to fully wet the powder and let it stand for 15-18 hours to promote water penetration between particles.
[0033] Ball milling: After removing the gas in the tank, start the ball mill for 20-24 hours of continuous ball milling to obtain a fine and uniform slurry.
[0034] Drying and sieving: Pour out the slurry, place it in an environment of 80-95°C and dry it to a suitable humidity, then sieve it through a 40-80 mesh screen to obtain particles of appropriate size.
[0035] Pre-sintering: The sieved powder is placed in a muffle furnace, slowly heated to 400°C at a heating rate of 5°C / min, and pre-sintered at this temperature for 5.5-6 hours to initially promote chemical reactions between powders and particle rearrangement.
[0036] Secondary ball milling and drying: After the pre-sintering, the powder is mixed with deionized water again and ball milled for a second time for 20-24 hours, followed by drying and sieving (80-110 mesh) to obtain a finer raw material to be formed.
[0037] 3. Molding and low temperature sintering
[0038] Molding preparation: Add 8wt% PVA adhesive to the sieved powder, grind thoroughly until evenly mixed, and sieve again through an 80-110 mesh sieve to ensure the fineness and fluidity of the powder.
[0039] Pressing: The processed raw material powder is placed in a mold and pressed into a cylindrical block with a diameter of 11.7 mm and a height of 5.45 mm under a pressure of 2 bar.
[0040] Stand and dry: Allow the pressed blocks to stand at room temperature for 8-10 hours to drain excess moisture from the surface and interior.
[0041] Ultra-low temperature sintering: The dried block was placed in a sintering furnace and first heated to 480°C at a heating rate of 5°C / min and maintained for 6 hours to volatilize the PVA adhesive. Subsequently, the temperature was continued to rise to the range of 500-620°C and sintered for 3 hours to allow the block to complete densification and crystal phase transformation at high temperature, and then cooled to room temperature with the furnace to obtain CoTeMoO6 ceramic sample 1.
[0042] Example 2
[0043] The difference from Example 1 is that the sintering temperature is 520°C, and a CoTeMoO6 ceramic sample 2 is obtained.
[0044] Example 3
[0045] The difference from Example 1 is that the sintering temperature is 540°C, and CoTeMoO6 ceramic sample 3 is obtained.
[0046] Example 4
[0047] The difference from Example 1 is that the sintering temperature is 560°C, and a CoTeMoO6 ceramic sample 4 is obtained.
[0048] Example 5
[0049] The difference from Example 1 is that the sintering temperature is 580°C, and CoTeMoO6 ceramic sample 5 is produced.
[0050] Example 6
[0051] The difference from Example 1 is that the sintering temperature is 600°C, and a CoTeMoO6 ceramic sample 6 is obtained.
[0052] Example 7
[0053] The difference from Example 1 is that the sintering temperature is 620°C, and a CoTeMoO6 ceramic sample 7 is obtained.
[0054] The CoTeMoO6 ceramic samples prepared in Examples 1 to 7 were analyzed by X-ray diffraction (XRD) patterns. Figure 1 As shown. Figure 1 It can be seen that the main diffraction peaks of CoTeMoO6 ceramics sintered at 500℃ to 620℃ are highly matched with the standard card PDF#01-089-8181, which conclusively proves that the CoTeMoO6 crystal phase with an orthorhombic structure (space group P21212(18)) was successfully synthesized during the sintering process. However, the spectrum also shows secondary diffraction peaks consistent with CoMoO4 (PDF#01-071-2505), which reveals that a certain amount of CoMoO4 secondary phase is inevitably produced during the synthesis process.
[0055] The presence of this secondary phase is a noteworthy phenomenon because it may have a significant impact on the airtightness properties of the final ceramic sample. Specifically, the presence of the CoMoO4 phase may increase the porosity or interface defects in the ceramic material, factors that are generally closely related to the degradation of dielectric properties, especially the increase in dielectric loss. Therefore, when preparing CoTeMoO6 ceramics, optimizing the sintering conditions to reduce or eliminate the formation of the CoMoO4 secondary phase is crucial to improving the airtightness of the ceramic and reducing the dielectric loss.
[0056] Further, the CoTeMoO6 ceramic samples prepared in Examples 1 to 7 were scanned by scanning electron microscope (SEM), and the SEM images were as follows: Figure 2 shown.
[0057] Depend on Figure 2 As can be seen from (a) in the figure, the microstructural characteristics of CoTeMoO6 ceramic sample 1, namely, the grain size is relatively small, and the average grain size (AG) is only 0.204μm, which indicates that the current sintering degree has not reached the optimal state and there is still room for further improvement. Figure 2 From the SEM image (b), it can be observed that in CoTeMoO6 ceramic sample 2, with the increase of sintering temperature, the grains show obvious growth behavior. This phenomenon may indicate a decrease in the number of grain boundaries inside the material, because the increase of grains is usually accompanied by the merging and reduction of grain boundaries. The measured average grain size (AG) is 0.423μm, which is an increase compared with the previous observations, further confirming the trend of grain growth. Figure 2 (c) is the SEM image of CoTeMoO6 ceramic sample 3. It can be seen that the grains are affected by the increase in temperature, which promotes their growth and the average grain size is 0.456μm. Figure 2 The SEM image of CoTeMoO6 ceramic sample 4 presented in (d) clearly shows the microstructure of the ceramic in this example, in which the grain morphology is more significant and the distribution is relatively uniform, and the average grain size measured reaches 0.66μm. This result not only shows the effective growth of grains during sintering, but also indicates that the material may have good crystallinity and low porosity, which may have a positive effect on the physical and dielectric properties of the ceramic. Figure 2 It can be visually observed in the SEM image (e) that the grain size distribution of CoTeMoO6 ceramic sample 5 is uniform, the number of pores is significantly reduced, the sintered body is highly dense, and the average grain size is measured to be 0.73 μm. Figure 2In the ceramic SEM image shown in (f), the growth state of the grains of CoTeMoO6 ceramic sample 6 shows a certain degree of inhomogeneity, which indicates that there may be local differences in the growth rate or conditions of the grains during the sintering process. Nevertheless, overall, the average size of the grains reached 0.933μm, showing a significant effect of the sintering process on grain growth. However, the inhomogeneity of grain growth may affect certain properties of the material and may deteriorate the dielectric properties of the ceramic sample. Figure 2 In the ceramic SEM image shown in (g), the average grain size of CoTeMoO6 ceramic sample 7 reached 0.973μm. However, it is worth noting that due to the high sintering temperature, some grains showed abnormal overgrowth, resulting in uneven grain size distribution. This uneven grain growth not only affects the aesthetics of the material's microstructure, but more importantly, the number of pores between grains increases significantly. These pores exist as defects and are likely to become the source of dielectric loss, which has an adverse effect on the dielectric properties of the ceramic. Figure 2 In (h), the grain size of the sample increases from 0.204μm to 0.977μm, indicating that the sintering temperature can promote grain growth.
[0058] Furthermore, the characterization density and relative density of the CoTeMoO6 ceramic samples prepared in Examples 1 to 7 were tested, and the results were as follows: Figure 3 shown.
[0059] Depend on Figure 3 It can be seen that the density of CoTeMoO6 ceramic sample 1 is ρ = 4.885 g / cm 3 ; Relative density ρ re =89.7%; the density of CoTeMoO6 ceramic sample 2 reached 4.95 g / cm 3 , relative density ρ re The density of CoTeMoO6 ceramic sample 3 is ρ = 5.017 g / cm 3 , relative density ρ re =92.25%; the characteristic density of CoTeMoO6 ceramic sample 4 is ρ=5.13 g / cm 3 , relative density ρ re =93.65%, and the density is significantly improved; the density of CoTeMoO6 ceramic sample 5 reaches the highest level, with a density of ρ = 5.247 g / cm 3 , relative density ρ reIt is as high as 95.94%, indicating that the internal structure of the material is compact and the porosity is low. This high density property indicates that the material may have low dielectric loss; the characterization density of CoTeMoO6 ceramic sample 6 is ρ = 5.13 g / cm 3 , relative density ρ re =93.82%, the sample density decreased; the density of CoTeMoO6 ceramic sample 7 decreased to 4.99 g / cm 3 , relative density ρ re It also decreased to 91.34%, which indicates that the density of the ceramic has decreased. It indicates that the dielectric properties of the ceramic may have deteriorated, because defects such as pores will intensify the scattering and absorption of electromagnetic waves in the material, thereby increasing the dielectric loss.
[0060] Finally, the dielectric properties of the CoTeMoO6 ceramic samples prepared in Example 1 to Example 7 were tested respectively, and the test results are shown in Table 1.
[0061] Table 1
[0062]
[0063] In summary, when the sintering temperature is set in the range of 560-600℃, the performance of CoTeMoO6 ceramics is particularly outstanding. The optimal sintering temperature is 580℃, which makes the ceramic material reach the optimal state in terms of dielectric properties.
[0064] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6, characterized in that: The following steps are involved: S1, taking cobalt monoxide powder, tellurium dioxide powder and molybdenum trioxide powder in a molar ratio of 1:1:1, and mixing them uniformly to obtain a mixed powder A; S2, adding the mixed powder A into deionized water, and performing the first ball milling to obtain a mixed slurry A; S3, drying the mixed slurry A, and passing it through a 40-80 mesh sieve after drying to obtain a mixed powder B; S4, heating the mixed powder B to 400°C and pre-sintering for 5.5-6 hours to obtain mixed powder C; S5, adding the mixed powder C into deionized water, and performing a second ball milling to obtain a mixed slurry B, drying the mixed slurry B, and passing it through a 40-80 mesh sieve after drying to obtain a mixed powder D; S6, adding 8 wt % of PVA adhesive to the mixed powder D, grinding thoroughly until uniformly mixed, and passing through an 80-110 mesh sieve to obtain a mixed powder E; pressing the mixed powder E into a shape; S7. After the formed block is allowed to stand at room temperature for 8-10 hours, it is placed in a sintering furnace, heated to 480°C, and maintained for 6 hours to volatilize the PVA adhesive; then, the temperature is continued to be raised to 500-620°C and sintered for 2-4 hours, and the furnace is cooled to room temperature to obtain a low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6.
2. The method for preparing the low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6 according to claim 1, characterized in that: The particle sizes of the cobalt monoxide powder, tellurium dioxide powder and molybdenum trioxide powder are all 350-400 meshes, and the purity of the cobalt monoxide powder, tellurium dioxide powder and molybdenum trioxide powder are all 99.0%-99.95%.
3. The method for preparing the low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6 according to claim 1, characterized in that: During the first and second ball milling, add an appropriate amount of deionized water to the ball mill to fully wet the powder, and let it stand for 15-18 hours to promote water penetration between particles; after removing the gas in the tank, start the ball mill for 20-24 hours of continuous ball milling to obtain a fine and uniform slurry.
4. The method for preparing the low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6 according to claim 1, characterized in that: The mixed slurry A and the mixed slurry B are both dried at 80-95°C.
5. The method for preparing the low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6 according to claim 1, characterized in that: In the step S4, heating is performed to 400° C. at a heating rate of 5° C. / min.
6. The method for preparing the low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6 according to claim 1, characterized in that: In the step S6, the material is pressed into a cylindrical block at a pressure of 2 bar.
7. The method for preparing the low-temperature and low-dielectric-loss microwave dielectric ceramic CoTeMoO6 according to claim 1, characterized in that: In the step S7, the sintering temperature is 560-600°C.
8. A low-temperature, low-dielectric-loss microwave dielectric ceramic CoTeMoO6 prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Niobium zinc barium-based microwave medium ceramic and preparation method thereof
CN101830708A
Composition for forming dielectric ceramic and dielectric ceramic material
CN114573335A
Molybdenum cobalt telluride heterostructure material and preparation method and application thereof
CN117658081A